PARP1 Upregulation in Recurrent Oral Cancer and Treatment Resistance - Wang, Feifei; Gouttia, Odjo G.; Wang, Ling; Peng, Aimin (Frontiers in Cell and Developmental Biology, 2022)
First-line treatments for oral cancer typically include surgery, radiation, and in some cases, chemotherapy. Radiation and oral cancer chemotherapeutics confer cytotoxicity largely by inducing DNA damage, underscoring the importance of the cellular DNA damage repair and response pathways in cancer therapy. However, tumor recurrence and acquired resistance, following the initial response to treatment, remains as a major clinical challenge. By analyzing oral tumor cells derived from the primary and recurrent tumors of the same patient, our study revealed upregulated PARP1 expression in the recurrent tumor cells. Cisplatin and 5-fluorouracil treatment further augmented PARP1 expression in the recurrent, but not the primary, tumor cells. Post-treatment upregulation of PARP1 was dependent on the catalytic activities of PARP and CDK7. Consistent with the established function of PARP1 in DNA repair, we showed that overexpression of PARP1 rendered the primary tumor cells highly resistant to DNA damage treatment. Conversely, PARP inhibition partially reversed the treatment resistance in the recurrent tumor cells; combinatorial treatment using a PARP inhibitor and cisplatin/5-fluorouracil significantly sensitized the tumor response in vivo. Taken together, we reported here PARP1 upregulation as a clinically relevant mechanism involved in oral cancer recurrence, and suggested the clinical benefit of PARP inhibitors, currently approved for the treatment of several other types of cancer, in oral cancer.